Cultures of America Polish Americans - Gabor, Al (Marshall Cavendish Corporation, 1995)
Provides a history of the ethnic group, their early immigration and lifestyles, and their contemporary customs and traditions
Keywords: Juvenile Nonfiction; Other; People & Places; United States